Rebound serum bilirubin levels after single vs. double phototherapy - Widyastuti, Widyastuti; Supriatmo, Supriatmo; Tjipta, Guslihan Dasa (Paediatrica Indonesiana, 2014)
Background Hyperbilirubinemia is the most common clinical phenomenon found in newborns. Phototherapy is the standard treatment for lowering bilirubin levels in neonates. While intensive (double) phototherapy produces a more rapid decline in serum bilirubin levels than standard (single) phototherapy, greater rebound effects may occur. Objective To assess bilirubin levels in neonates with hyperbilirubinemia who underwent single or double phototherapy, including rebound bilirubin levels after phototherapy termination. Methods An open, randomized, controlled trial was con ducted at H. Adam Malik Hospital and Dr. Pirngadi Hospital, Medan, from August 2009 until January 2010. Subjects with indirect hyperbilirubinemia were divided into two groups. One group received single phototherapy (n = 41) and other received double photo therapy (n = 40) . Measurements of total plasma bilirubin level were conducted at 12 hours and at 24 hours of phototherapy, as well as at 24 hours after phot otherapy termination. Rebound bilirubin serum level was defined as an increment of about 1 - 2 mg/dL serum bilirubin after phototherapy discontinuation. Results The decreases in serum bilirubin levels were significantly greater in the do uble phototherapy group for observations at 12 h ours , 24 h ours, and 24 hours after phototherapy t ermination (P = 0.0001). At the 24-hour observation after terminationofphototherapy, only 1 neonate (2.7%) in the single phototherapy group compared to 4 neonates (10.8%) in the double phototherapy group had serum bilirubin level increases of 1 - 2 mg/dL. Fisher’s exact test did not reveal a significant difference in rebound serum bilirubin occurrence in the two groups (P = 0.358). Conclusion Double phototherapy shows significantly greater decrease in bilirubin level compared to single phototherapy within a same period of time. Rebound serum bilirubin levels after single and double phototherapy may occur in some patients with hyperbilirubinemia, as bilirubin production continues. However, 260 â€¢ Paediatr Irulones, Vol. 54, No. 5, September 2014 there is no significant difference in rebound effects between single vs. double phototherapy.